Pembuatan Macroporous Microcarrier Berbahan Baku Hydroxyapatite Menggunakan Kuning Telur Sebagai Agen Pembentuk Pori - Dwi Yerlis Rahmi; Ahmad Fadli; Idral Amri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Porous hydroxyapatite is a crystalline molecule composed of calcium and phosphorus which can be used as a macroporous microcarrier. Macroporoous microcarrier is one of tissue engineering technology that consist of support matrix and can be used as a cell culture medium in bioreactor. Protein foaming-starch consolidation method is choosed for manufacturing porous hydroxyapatite with egg yolk as a pore-forming agent. The purpose of this research is to study the influence of process variables i.e yolk addition (27 - 33 gr), sintering temperature (1200oC - 1300oC), and drying temperature (170oC - 190oC) toward porous hydroxyapatite properties such as compressive strenght, porosity and pore size made by protein foaming – starch consolidation methode. The experimental resulted porous hydroxyapatite with compressive strength in range of 4.55 - 11.05 MPa, porosity in rang of 25.95 - 58.74% and pore size in range of 15.08 - 33.56 μm.Keywords: compressive strength, pore size, porosity, porous ceramic